High-Grade Stenosis of a Traumatic Brachiocephalic Pseudoaneurysm and the Change in Cerebral Blood Flow Assessed With Transcranial Doppler Ultrasound. Issue 2 (June 2021) - Nguyen, Winnie; Albanese, Tammy; Tran, Vanessa; Moore, Anne; Sekhar, Laligam
This is a case report of a 35-year-old female pedestrian struck by a semi-truck. computed tomographic angiography (CTA) revealed a pseudoaneurysm at the proximal brachiocephalic artery measuring 1.8 cm in cranio-caudal length and 1.2 × 0.6 cm transverse. Just distal to the pseudoaneurysm, there was severe luminal narrowing caused by either a dissection flap or mural thrombus. Due to profound left-sided weakness, transcranial Doppler ultrasound was performed which demonstrated "hesitant" waveforms in the right middle cerebral and right vertebral arteries secondary to proximal obstruction. Hesitant waveforms display mid-systolic velocity deceleration and may also be referred to as the "bunny" waveform. Emboli monitoring of the right middle cerebral and basilar arteries were positive for active embolization